Antiferroelectric Anisotropy of Epitaxial PbHfO3 Films for Flexible Energy Storage. (28th July 2021) - Tsai, Meng‐Fu; Zheng, Yun‐Zhe; Lu, Si‐Cheng; Zheng, Jun‐Ding; Pan, Hao; Duan, Chun‐Gang; Yu, Pu; Huang, Rong; Chu, Ying‐Hao
Abstract: Dielectric capacitors are widely studied for power supply systems because they can quickly store and release electrical energy. Among various kinds of dielectric materials, antiferroelectrics show promising features of high energy‐storage density and efficiency. In this study, epitaxial antiferroelectric PbHfO3 films with different orientations are fabricated, in which remarkable anisotropies of polarization and energy storage properties are discovered. With the optimization of film orientation, much‐improved energy density and excellent high‐temperature efficiency are achieved in the PbHfO3 films. Moreover, the PbHfO3 films are fabricated onto flexible mica substrates, which exhibit excellent property robustness against mechanical bending. This study provides a fundamental understanding of the anisotropic antiferroelectric behaviors of epitaxial PbHfO3 films and provides a generalizable pathway for flexible energy‐storage dielectric capacitors. Abstract : In this study, epitaxial antiferroelectric PbHfO3 films with different orientations are fabricated. With the optimization of film orientation, excellent high‐temperature efficiency is achieved in the PbHfO3 films. Moreover, the PbHfO3 films are fabricated onto flexible mica substrates, which exhibit excellent property robustness against mechanical bending. This study provides a fundamental understanding of the anisotropic antiferroelectric behaviors of epitaxial PbHfO3 films.